Understanding typology of residents living in disaster prone-area - Amin Choirul; Sukamdi; Rijanta (MATEC Web of Conferences, 2018)
Research about population immobility associated with disaster is very limited. This causes a lack of understanding about population immobility in disaster-prone areas. This research contributes to understanding population immobility by explaining the typology of residents who remain stay in disaster-prone areas. The survey was conducted among the residents of Kampong Tambak Lorok Semarang, which is prone to rob inundation (rob). The research sample was 235 heads of households selected using proportional sampling area technique. Data was collected using a questionnaire consisting of two parts: (1) demographic, social, and economic characteristics of people who did not move from disaster-prone areas; and (2) staying intention in disaster-prone areas. Data was analyse using descriptive analysis by using the table and graph of respondent characteristic and relation between respondent characteristics and the staying intention in the research area. Three (3) typologies have been identified, namely: Type-1 are residents who wish to stay; Type-2 are residents who still have not decided whether to stay or move; Type-3 are residents who do not want to stay. Each of these typologies is described by place of birth, age, length of stay, education, occupation, and income. Understanding the typology of residents living in disaster-prone areas is important for inputs for policy-makers, especially regarding the relocation of people from disaster-prone areas to be more effective.